Activity Test of Neem Leaf (Azadirachta Indica A. Juss) Anti-Dambry Shampoo on Fungus (Malassezia Furfur) - Ginting, Mandike; Septiana, Lilik; Br. Ginting, Grace Anastasia (International Archives of Medical Sciences and Public Health, 2023)
Background; Dandruff is a disorder in the form of excessive flaking of dead skin on the scalp, sometimes accompanied by itching and inflammation. One of the causes of dandruff is the Malassezia furfur fungus. Neem leaves contain the main active ingredients of neem, namely azadirachtin, meliantriol, nimbin, nimbidin and salanin, substances that are known to be effective as insecticides. Objective; The aim of the study was to determine the formulation of anti-dandruff shampoo preparations of ethanol extract of neem leaves (Azadirachta indica A. Juss) and Activity Test against Fungus (Malassezia furfur). Method; The research method was experimental, which included taking plants, making simplicia, formula for neem leaf extract shampoo (2%, 4%, 6% and 8%), evaluating preparations and testing antifungal activity. Results; The results of the study were based on organoleptic tests, the preparations were white and brown in color, had a distinctive neem aroma and were viscous in shape; there is no coarse grain in the preparation; pH of preparations F0 (6.0), F1 (5.5), F2 (5.3), F3 (5.3) and F4 (5.2); foam height tests F0 (8 cm), F1 (8.5 cm), F2 (8.7 cm), F3 (9 cm) and F4 (9.5 cm); there is no itching, redness and swelling on the skin of the volunteers; stability test does not change color, aroma and shape of the preparation; antifungal test preparations F0 (0 cm), F1 (11.65 cm), F2 (12.73 cm), F3 (12.86 cm), F4 (13.61 cm) and K+ (22.8 cm). Conclusion; The conclusion of the research is that the ethanol extract of neem leaves (Azadirachta indica A. Juss) can be formulated as a shampoo that meets the requirements for physical evaluation and inhibits the growth of fungus (Malassezia furfur) at a concentration of 8% (13.61 mm) best.